2016
DOI: 10.1038/srep29106
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statins on prostate cancer recurrence and mortality after definitive therapy: a systematic review and meta-analysis

Abstract: In this work, we aim to further analyze the association of statins use with biochemical recurrence (BCR) of prostate cancer (PCa) and PCa-specific mortality after definitive therapy. A systematic literature search of PubMed, MEDLINE, and EMBASE through Jul 2015 was conducted. Pooled Hazard ratio (HR) estimates with corresponding 95% confidence intervals (CIs) were calculated using random-effects model. STATA version 10 (Stata corporation, college station, TX) was employed to conduct all statistical analyses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
4
29
0
1
Order By: Relevance
“…These results are consistent with reports that pharmaceutical interventions, e.g. statins that target cholesterol metabolism, are associated with reduced prostate cancer recurrence [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with reports that pharmaceutical interventions, e.g. statins that target cholesterol metabolism, are associated with reduced prostate cancer recurrence [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Statins, a class of cholesterol-lowering medications that inhibit 3-hydroxy-3-methl-glutaryl-coenzyme A reductase, are also substrates of SLCO2B1 and have been shown to act as an anticancer drug in various types of cancers [ 35 ]. In PCa, clinical studies have shown the controversial results in statin treatment after RP [ 36 39 ]. It has been reported that DHEAS uptake is inhibited by statins in PCa cell lines [ 40 ], and statin treatment decreased castration resistant progression with lower intra-tumoral androgen levels in murine models [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to nonusers, statin use has been associated with reduced risk of advanced prostate cancer and enhanced biochemical relapse‐free survival after either radical prostatectomy or radiation therapy in several epidemiological studies . Statin users have also been reported to have improved prostate cancer‐specific survival compared to nonusers, especially in the context of androgen deprivation therapy . Improved progression‐free and disease‐specific survival among statin users have also been reported after radical prostatectomy, although not all studies agree .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Statin users have also been reported to have improved prostate cancer-specific survival compared to nonusers, especially in the context of androgen deprivation therapy. [9][10][11] Improved progression-free and disease-specific survival among statin users have also been reported after radical prostatectomy, 12 although not all studies agree. 13 Survival benefits are likely to depend on treatment compliance, as lowered risk of disease recurrence has been observed only in men whose serum cholesterol decreases after statin intervention.…”
Section: Introductionmentioning
confidence: 99%